Structured assessment and followup for patients with hereditary kidney tumour syndromes - Lattouf, Jean-Baptiste (Can Urol Assoc J, 2016)
INTRODUCTION: Optimal clinical assessment and subsequent followup of patients with or suspected of having a hereditary renal cell carcinoma syndrome (hRCC) is not standardized and practice varies widely. We propose protocols to optimize these processes in patients with hRCC to encourage a more uniform approach to management that can then be evaluated. METHODS: A review of the literature, including existing guidelines, was carried out for the years 1985–2015. Expert consensus was used to define recommendations for initial assessment and followup. RESULTS: Recommendations for newly diagnosed patients’ assessment and optimal ages to initiate followup protocols for von Hippel Lindau disease (VHL), hereditary papillary renal cancer (HPRC), hereditary leiomyomatosis with renal cell carcinoma (HLRCC), Birt-Hogg-Dubé syndrome (BHD), familial paraganglioma-pheochromocytoma syndromes (PGL-PCC), and tuberous sclerosis (TSC) are proposed. CONCLUSIONS: Our proposed consensus for structured assessment and followup is intended as a roadmap for the care of patients with hRCC to guide healthcare providers. Although the list of syndromes included is not exhaustive, the document serves as a starting point for future updates.